Penerapan Metode Multisensori untuk Kemampuan Membaca Permulaan pada Siswa Kelas I di SD X Bangkalan - Nurushshiyam Rahmawati; Lena N. Pandjaitan (Universitas Muhammadiyah Jember, 2020)
Pre-reading ability is the process of learning to read in the early grades, to recognize writing as a symbol or language symbol to voice the writing. The Ministry of National Education stated that grade I SD is expected to be able to read simple texts fluently with correct pronunciation and intonation. Some students are not fluent in reading because they have difficulty remembering letters so they are choked up. One of the factors that affect students' ability to read words is the teaching method. Based on previous studies, the multisensory method is quite effective in increasing pre-reading skills. The multisensory method in teaching literacy is a learning process that utilizes visual sensory (sight), auditory (hearing), kinesthetic-tactile (movement, touch) to improve memory. This study used a quasi-experimental method. The research instrument used an IRA (Informal Reading Assessment). The results of the application of the multisensory method showed that there was an increase in score and a higher category change in the aspect of pronouncing the sound of letters and words (phonics) and the aspect of reading fluency.